Cyperus eragrostis Lam. (Cyperaceae), nueva localidad para Andalucía Occidental - Devesa, Juan Antonio (Acta Botanica Malacitana, 2015)
Cyperus eragrostis Lam. (Cyperaceae), a new record to the Western Andalusia Palabras clave. Cyperaceae, Cyperus, Península Ibérica Key words. Cyperaceae, Cyperus, Iberian Peninsula